Perjuangan Perempuan Kepala Keluarga dalam Menghadapi Stigma Sosial: Studi Kasus Perempuan Penjual Ikan Bakar - Dwi Kurniawati Kurniawati (Pusat Studi Wanita dan Keluarga UGM, 2022)
Female heads of household are faced with social stigma, and on the other hand, demands to meet the economic needs of the family independently. This study aims to determine the efforts of women heads of families in dealing with social stigma. The research approach used in this research is qualitative with an exploratory case study. The technique of determining the informants in this study used purposive sampling. The data collection techniques include observation, interviews, and documentation. The unit of analysis used in this study is the individual, namely the female head of the family in the face of social stigma, analyzed using Froma Walsh's thinking. Female heads of household face social stigma in the form of, The assessment or perception of their environment, which considers them to be inferior if they are decorated, is considered a temptress to attract buyers' attention, is considered to be a grab for someone's husband for those who have polygamous status, and is often talked about the ugliness of their household. Efforts made by female heads of household in dealing with social stigma. Using the sub-dimensional belief that every problem has a solution, the sub-dimensional pattern of organization with the family, and the sub-dimension of the communication process so that the environment accepts it well.